Low-Grade Heat Recovery: Emerging Materials and Systems for Efficient Utilization - Sai Preetham Anumasu (International Journal of Energy and Thermal Applications, 2025)
Low-grade heat (LGH), generally characterized by temperatures below 200°C, constitutes a significant portion of wasted thermal energy in industrial, commercial, and even residential processes. Despite its vast availability, the efficient recovery and utilization of LGH remains underdeveloped due to its inherently low exergy content and the limitations of traditional heat recovery technologies. The creation of cutting-edge materials and creative system-level approaches for LGH recovery has accelerated significantly as companies continue to look for sustainable and energy-efficient solutions. This review critically examines the current landscape of LGH recovery, emphasizing emerging materials such as thermoelectric compounds, phase change materials, nanofluids, and metal-organic frameworks, all of which offer unique thermal, electrical, or adsorptive properties that enhance energy conversion efficiency. Additionally, system-level technologies such as the Organic Rankine Cycle (ORC), thermoelectric generators, absorption/adsorption cooling, and hybrid thermal conversion mechanisms are analyzed for their performance, integration potential, and practical limitations. The synergy between materials and system design plays a crucial role in improving the viability of LGH recovery across various sectors, including power generation, automotive exhaust recovery, building energy systems, and data center thermal management. The study also explores the techno-economic feasibility, scalability, and lifecycle sustainability of these technologies, while addressing key challenges such as cost, material durability, and operational complexity. Future perspectives are provided, highlighting opportunities for smart monitoring, modular integration, and the role of artificial intelligence in optimizing LGH utilization. Overall, this review offers a comprehensive understanding of how novel materials and engineering innovations are reshaping the potential of low-grade heat recovery and contributing to global energy efficiency goals and decarbonization efforts.
Keywords: Low-grade heat; Phase change materials; Waste heat recovery; organic Rankine cycle; thermal energy conversion; thermoelectric materials